Factors Influencing the Listening Skills of Grade 10 Students for the Development of Audio Material - QUINILOG, EDNA (International Journal of Arts, Sciences and Education, 2025)
The study examined the demographic profile of students and their reception of audio material as a teaching tool. Findings revealed that Tagalog students slightly outnumbered those who spoke Ilokano and Hiligaynon. In terms of technological devices used for listening, smartphones had the highest usage, followed by television and radio. Most students reported giving full attention when listening, often using notes or accompanying books to aid comprehension. However, challenges remained in maintaining focus, particularly among students who listened without full attention. External factors such as environmental noise and competing technologies influenced listening either positively or negatively. Additionally, internal factors like emotional state and teacher strategies significantly affected attention and comprehension.The study further determined that the audio materials were of high quality and well-received by students. They’re valid in terms of objectives, content, design, and technical quality, indicating thoughtful development and effective delivery. Student reception was highest regarding the presentation and format, although content could still be improved. Technical quality emerged as a key factor in student engagement. Importantly, a meaningful correlation was identified between the students’ demographic characteristics and their reception of audio materials, suggesting that student characteristics influence learning preferences and effectiveness. This underscores the importance of considering student diversity when developing instructional materials. The study recommends continuous enhancement of audio-based tools, with attention to demographic differences and factors affecting student attention. By optimizing content and addressing distractions, educators can design learning environments that are inclusive and responsive to diverse needs student needs and improve listening outcomes.